1994
DOI: 10.1063/1.111231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wafer bow and warpage on the integrity of thin gate oxides

Abstract: Effect of wafer bow on electrostatic chucking and back side gas cooling Estimation of wafer warpage profile during thermal processing in microlithography Rev. Sci. Instrum. 76, 075111 (2005); 10.1063/1.1979468 Modeling of direct wafer bonding: Effect of wafer bow and etch patterns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…It is well reported that the hot-carrier reliability in MOSFET is signicantly improved by smoothing the surface, homogenous interface state, and a low defects in the near drain junctions; however the MOSFETs did not consider the substrate thermal stress due to is extremely low stress level. [28][29][30] The thermal substrate stress can affect several factors, such as grain boundary density, microcracks, interface bonding state, and surface smoothness.…”
Section: Resultsmentioning
confidence: 99%
“…It is well reported that the hot-carrier reliability in MOSFET is signicantly improved by smoothing the surface, homogenous interface state, and a low defects in the near drain junctions; however the MOSFETs did not consider the substrate thermal stress due to is extremely low stress level. [28][29][30] The thermal substrate stress can affect several factors, such as grain boundary density, microcracks, interface bonding state, and surface smoothness.…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors contributing to wafer warpage, such as coefficient of thermal expansion (CTE) mismatch, thickness of films and pattern density [4][5]. Wafer warpage induced stress is one of the root causes leading to process and device failure such as delamination, cracking, and decrease in device performance [6][7]. Therefore, it is crucial to reduce wafer warpage through process optimization for TSV wafer.…”
Section: Introductionmentioning
confidence: 99%
“…This plastic deformation gives rise to pattern misalignment, device failure, generation of defects in dielectric films, etc. 1 Much effort has been made to study this problem of thermal stress in RTP. Vandenabeele et al showed direct experimental evidence that pattern induced temperature nonuniformity could cause plastic deformation.…”
Section: Introductionmentioning
confidence: 99%